Role Model Of The Education Council On The Performance Of Madrasah Principals And Madrasah Teachers (Private) In Bekasi District - Lutfan Son’any; Irwan Prayitno; Iswan Iswan (PT Publikasiku Academic Solution, 2024)
Research on the Role Model of the Education Council on the Performance of Madrasah Principals and Madrasah Teachers, conducted by sampling 9 madrasahs in Bekasi District, utilizes both quantitative (questionnaires) and qualitative (interviews, observations, and document analysis) methods. The study addresses the lack of attention to education in madrasahs from local governments and relevant educational institutions. This lack of attention leads to various issues regarding madrasah services, facilities, curriculum, performance, low student enrollment, and madrasah output. These issues need to be addressed seriously through oversight from institutions overseeing education, including the Education Council. This institution plays a quantitative control role and three qualitative roles: Advice, Support, and Mediator. Implementing teaching approaches tailored to the characteristics of madrasah principals and teachers is essential. The research adopts a descriptive approach with qualitative methods. Data collection procedures include observation, interviews, and documentation. Data analysis is conducted interactively and continuously. The findings indicate that the role of the Education Council in improving education quality in Bekasi District still has many shortcomings due to the lack of implementation of the institution's work programs. In conclusion, the role of the Education Council in enhancing education quality in Bekasi District is not optimally executed. The research benefits from understanding and exploring the extent to which the model of the Education Council's role affects the quality of education services, especially for Islamic educational institutions such as madrasahs at the elementary, junior high, and high school levels.